(untitled) (Research, Society and Development, 2020)
In Brazil, wine production can be identified as an activity characteristic of the South region, especially in the state of Rio Grande do Sul. However, the cultivation of grapes and consequent production of wine has spread to new areas. The state of Goiás is a good example of this process. As the production of grapes and wines outside the traditional regions can be seen as an innovation, we chose to analyze the activity from the entrepreneurial perspective, specifically rural entrepreneurship. The research was conducted through semi-structured interviews, during the on-site visits in the municipalities of Cocalzinho de Goiás, Itaberaí, and Paraúna. The results found that the development of viticulture in Goiás was motivated by the great appreciation of the entrepreneurs for the production of grapes and wines. They also see in the Cerrado a good business opportunity, and despite the great challenges inherent to the activity, believe in the potential of wines with the terroir of the Cerrado.